2021
DOI: 10.1186/s12885-021-08257-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of peptide receptor radionuclide therapy in advanced radioiodine-refractory differentiated thyroid cancer and metastatic medullary thyroid cancer: a systematic review

Abstract: Background It has been shown that a subgroup of patients with differentiated thyroid cancer (DTC) and medullary thyroid carcinoma (MTC) would progress to advanced stages of thyroid cancer. Therefore, the present study was done to systematically review available evidence in order to investigate efficacy and safety of peptide receptor radionuclide therapy (PRRT) in the patients with advanced radioiodine refractory differentiated thyroid cancer (RR-DTC) and metastatic MTC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 52 publications
0
20
0
2
Order By: Relevance
“…Furthermore, in a different cohort of 42 patients, almost 40% of them showed PD ( 198 ). Recently, a meta-analysis reviewed the efficacy of PRRT in patients with MTC, evaluating data from 220 patients ( 199 ). Unfortunately, the type of PRRT used was not described in 51 patients, most of the other patients were treated with 177Lu-based agent (n=157) and only a minority with 111In-based agent (n=12).…”
Section: Beyond Mkis and Highly Selective Inhibitorsmentioning
confidence: 99%
“…Furthermore, in a different cohort of 42 patients, almost 40% of them showed PD ( 198 ). Recently, a meta-analysis reviewed the efficacy of PRRT in patients with MTC, evaluating data from 220 patients ( 199 ). Unfortunately, the type of PRRT used was not described in 51 patients, most of the other patients were treated with 177Lu-based agent (n=157) and only a minority with 111In-based agent (n=12).…”
Section: Beyond Mkis and Highly Selective Inhibitorsmentioning
confidence: 99%
“…A total of 157 RAI-R DTC patients were treated with PPRT. Biochemical and objective responses (partial and complete) were observed in 25.3 and 10.5% of patients, respectively [ 81 ]. The main adverse events were nausea, asthenia, and transient hematologic toxicity.…”
Section: Advanced and Radioactive Iodine Refractory Cancermentioning
confidence: 99%
“…Discontinuation of treatment due to toxicity is reported in only 1.3% of cases, hemotoxicity grade III–IV in 6.5% of cases, and nephrotoxicity grade III–IV in 0.8% [ 128 ]. Maghsoomi et al in a systematic review among 220 patients with metastatic MTC demonstrated biochemical and objective responses (partial and complete) in 37.2 and 10.6% of patients, respectively [ 81 ]. Satapathy et al showed that the disease control rate could be even higher (86%) if combining PRRT with a radiosensitizer, e.g., capecitabine [ 133 ].…”
Section: Medullary Thyroid Cancermentioning
confidence: 99%
“…Additional studies are warranted to assess effectiveness. A systematic review of 41 papers evaluating the use of PRRT in a subgroup of patients with SSTR positive radioiodine-refractory differentiated thyroid cancer and metastatic medullary thyroid cancer showed biochemical responses of 25.3-37.2% and objective response in 10.5-10.6%, with few adverse events identified [171]. It should be noted that individual study sizes were variable and the types of PRRT used, and patient populations were heterogenous, so the review concluded that multi-center randomized controlled trials are recommended to validate against other currently available treatments.…”
Section: Future Directions For Prrtmentioning
confidence: 99%